Kualitas Laporan Keuangan Konsolidasi : Pengaruh Pengendalian Internal dan Struktur Kepemilikan pada Perusahaan Publik - Rifat Thufail Achmad; Hendra Witanto; M. Masrukhan (Populer: Jurnal Penelitian Mahasiswa, 2024)
This study aims to analyze how internal control and ownership structure influence the quality of consolidated financial statements in public companies in Indonesia. The research adopts a literature review approach to analyze the impact of internal control and ownership structure on the quality of consolidated financial statements in public companies. Data was obtained through relevant secondary literature, such as academic papers, books, and research reports related to the impact of ownership structure changes on the consolidated financial statements of companies in Indonesia. The researcher conducted a literature search through online databases, such as Google Scholar, using relevant keywords and only considering trustworthy and relevant findings. The researcher also expanded the review by considering various perspectives to gain a more comprehensive understanding. The results of the study are divided into several main sections, including the quality of financial statements, consolidated financial statements, and the impact of internal control and ownership structure on public companies. The study concludes that strong internal control has a significant positive impact on the quality of consolidated financial statements, acting as a mechanism to prevent fraud and maintain the integrity of financial data. Strict controls improve compliance with accounting standards, making the reports more transparent and reliable. In addition, institutional ownership has been proven to have a significant positive impact on the quality of financial statements, as it encourages transparency and external oversight. However, managerial ownership does not show a significant impact, indicating that the incentives from managerial stock ownership are not strong enough to influence the improvement of financial statement quality.